2019
DOI: 10.1186/s42826-019-0026-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteins differentially expressed by glutamate treatment in cerebral cortex of neonatal rats

Abstract: Glutamate leads to neuronal cell damage by generating neurotoxicity during brain development. The objective of this study is to identify proteins that differently expressed by glutamate treatment in neonatal cerebral cortex. Sprague-Dawley rat pups (post-natal day 7) were intraperitoneally injected with vehicle or glutamate (10 mg/kg). Brain tissues were isolated 4 h after drug treatment and fixed for morphological study. Moreover, cerebral cortices were collected for protein study. Two-dimensional gel electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…We previously showed that glutamate exposure induces neuronal cell damage in neonates by up-and down-regulation of specific proteins (Kang et al, 2019). Damaged neurons with atypical round shapes and shrunken dendrites were found in cells from the glutamate-treated cerebral cortex [14]. The number of anomalous neurons was increased by glutamate exposure.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We previously showed that glutamate exposure induces neuronal cell damage in neonates by up-and down-regulation of specific proteins (Kang et al, 2019). Damaged neurons with atypical round shapes and shrunken dendrites were found in cells from the glutamate-treated cerebral cortex [14]. The number of anomalous neurons was increased by glutamate exposure.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, glutamate increases intracellular calcium levels and induces mitochondrial dysfunction [16]. We previously showed that glutamate exposure induces neuronal cell damage in neonates by up-and down-regulation of specific proteins (Kang et al, 2019). Damaged neurons with atypical round shapes and shrunken dendrites were found in cells from the glutamate-treated cerebral cortex [14].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…MCAO damage induces reduction of proteasome subunit alpha types 1 and 3, and retinoic acid alleviates decreases in these proteins. We previously showed decrease of proteasome subunit alpha in glutamateexposed cerebral cortex [45]. Decrease of these proteins is involved in cerebral cortex damage during neuronal development [45].…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, PP2A subunit B is considered an important factor in maintaining neurobiological function. We have previously shown that glutamate exposure causes neonatal cerebral cortical damage by regulating various proteins [15]. We assume that glutamate exposure controls the PP2A subunit B protein during brain development, causing neuronal damage.…”
Section: Introductionmentioning
confidence: 98%